Moderate partially skimmed milk consumption is associated with reduced mortality risk. (20th October 2021) - Ruggiero, E; Di Castelnuovo, A; Costanzo, S; Esposito, S; Persichillo, M; Cerletti, C; Donati, MB; de Gaetano, G; Iacoviello, L; Bonaccio, M
Abstract: Background: Data on milk and other dairy products intake with health outcomes are inconsistent. We investigated the association of milk and total dairy consumption with the risk of all-cause and cause-specific mortality in a Mediterranean population. Methods: We performed a longitudinal analysis on 22, 889 men and women (mean age 55.4±11.7 y; 52.3% women), from the Moli-sani Study cohort (enrollment 2005-2010) followed-up for a median of 11 years. Dietary data were collected through a 188-item food frequency questionnaire. Total dairy consumption (g/d) was calculated as the sum of milk (whole and partially-skimmed, g/d), yogurt (whole and partially skimmed, g/d) and cheese (fresh and hard, g/d). Hazard ratio (HRs) with 95% confidence interval (CI) were calculated by multivariable Cox regression, modelled by spline curves. Results: In multivariable-adjusted analysis controlled for sociodemographic, clinical and dietary factors, cheese, yogurt or whole milk intake were not associated with either all-cause or cause-specific mortality (p for overall association >0.38), as well as was total diary intake (p > 0.18). On the contrary, non-linear J-shaped curves were observed for the association of partially skimmed milk intake with all-cause and cancer mortality (p value for total and non-linear association=0.0072 and 0.035, and 0.097 and 0.049, respectively; magnitude of the relative reduction =16% and 18% at nadir of 128 and 114 g/d, respectively). A linear association between partially skimmed milk intake and CVD mortality was observed (p for association =0.047; p for non-linearity= 0.41), with HR = 0.82 (95%CI: 0.68-0.98) at 125 g/d and a window of statistically significant protection ranging from 100 to 250 g/d. Conclusions: In a large Mediterranean population of adults, consumption of 1 standard cup of partially skimmed milk was associated with lower all-cause, cancer and CVD mortality. Other dairy sources were not associated with mortality. Key messages: In a large Mediterranean population, total dairy intake did not predict mortality. Daily consumption of 1 standard cup of partially skimmed milk lowers the risk of all-cause, cardiovascular and cancer mortality.